Smarter Actuator Design with Complementary and Synergetic Functions. (23rd June 2015) - Khaldi, Alexandre; Plesse, Cedric; Vidal, Frederic; Smoukov, Stoyan K.
<x xml:space="preserve">Abstract</x> A general synthetic strategy for multifunctional actuators is presented, by confining desired functions in separate domains of interpenetrating polymer network materials. Specifically, complementary ionic actuator and shape‐memory functions are demonstrated by simultaneous, orthogonal reaction pathways. Synergistic effects also allow dynamic programming and two‐way linear shape‐memory actuation.